Neoalbaconol inhibits angiogenesis and tumor growth by suppressing EGFR‐mediated VEGF production. Issue 5 (May 2017) - Yu, Xinfang; Li, Wei; Deng, Qipan; You, Shuo; Liu, Haidan; Peng, Songling; Liu, Xiaolan; Lu, Jingchen; Luo, Xiangjian; Yang, Lifang; Tang, Min; Weng, Xinxian; et al.
Abstract : Neoalbaconol, derived from Albatrellus confluens, shows anti‐cancer activities in the previously study, but its role in angiogenesis is unknown. Here, we determined whether neoalbaconol could attenuate angiogenesis and how does it occur. Data demonstrated that neoalbaconol could inhibit the proliferation of breast cancer cells and induce apoptosis. Also, neoalbaconol suppressed vascular endothelial growth factor (VEGF)‐induced human umbilical vascular endothelial cells (HUVECs) proliferation, migration, invasion, and capillary‐like tube formation in vitro and reduced tumor angiogenesis in vivo . VEGF receptor activation and the downstream signal transduction cascades activation were inhibited by neoalbaconol. Additionally, neoalbaconol blocked EGFR‐mediated VEGF production. EGFR overexpression reversed the neoalbaconol‐induced VEGF reduction, confirming the importance of the EGFR inhibition in anti‐angiogenesis of neoalbaconol. Furthermore, neoalbaconol inhibited tumor growth and tumor angiogenesis in a breast cancer xenograft model in vivo . Taken together, these results indicate that neoalbaconol could inhibit tumor angiogenesis and growth through direct suppression effects on vascular endothelial cells and reduction of proangiogenic factors in cancer cells.